The Effect of Return On Asset (ROA), Debt to Equity Ratio (DER), and Earning Per Share (EPS) on Stock Prices in the Mining Sector on the Indonesia Stock Exchange for the 2015 - 2019 Period - Setiawan, Andri; Bayu Aji Sumantri, Muhammad (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Stock Exchange is a market where a company is buying and selling securities. In Indonesia, this place of buying and selling is known as Indonesia Stock Exchange (IDX). Companies listed on the stock exchange are companies that are open to the public. In the data presented by the IDX, there are several companies with different sectors. This study aims to examine the effect of Return on Asset (ROA), Debt to Equity Ratio (DER), and Earning Per Share (EPS) on share prices in mining sector companies on the Indonesia Stock Exchange from 2015 to 2019. The population in this study are 48 companies and the number of samples studied after going through thestage purposive sampling was 32 companies. The population in this study are mining sector companies listed on the IDX. Data analysis using Fixed Effect Model from panel data regression analysis. The method used in this research is descriptive and verification methods with quantitative analysis. The results showed that the variable Debt to Equity Ratio (DER) had no significant effect on stock prices. Meanwhile, Return on Asset (ROA) and Earnings per Share (EPS) have a positive and significant effect on stock prices. The results of this study are expected that the variable Return on Assets (ROA), Debt to Equity Ratio (DER), and Earnings per Share (EPS) can be used as a reference, both by company management and by investors in determining the right investment strategy